Hygroscopicity of ‘sucupira-branca’ (Pterodon emarginatus Vogel) fruits - Daniel E. C. de Oliveira; Osvaldo Resende; Lílian M. Costa; Glicélia P. Silva; Juliana de F. Sales (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT ‘Sucupira-branca’ (Pterodon emarginatus Vogel) is a tree from ‘Cerrado’ and stands out mainly for its pharmacological properties; however, there are no technological information about its post-harvest operations. Thus, the aim of this study was to determine the sorption isotherms of ‘sucupira-branca’ fruits for different air conditions and obtain the values of desorption isosteric heat, depending on the equilibrium moisture content of the product. The equilibrium moisture content of ‘sucupira-branca’ fruits was determined by dynamic method for temperatures of 25, 30, 35 and 40 °C and water activities for each temperature between 0.270 and 0.775. The models Chung-Pfost, Copace, Modified Halsey, Oswin Modified and Sigma Copace obtained high coefficient of determination (R2) and low chi-square (χ2), relative mean error (P) and estimated mean error (SE), and the Copace model was selected to represent the desorption isotherms. The isosteric heat increases with the reduction of equilibrium moisture content and required more energy to remove water from the ‘sucupira-branca’ fruit.